Exploration of Smoking Behavior of Adolescent Girls in Makassar City - Ibnu, Indra Fajarwati (Jurnal Kesmas Jambi, 2025)
Smoking behavior among adolescent girls is increasingly observed in many large cities, including Makassar City. The background of this study is to understand the factors that influence smoking behavior among adolescent girls, who often experience distinct social and psychological dynamics compared to other adolescent groups. This study aims to explore the motivations, social environmental influences, and perceived health risks related to smoking behavior among adolescent girls in Makassar City. This study used a qualitative approach with in-depth interviews with 10 adolescent girls who smoke, selected by purposive sampling from various high schools in Makassar. Data analysis was conducted thematically to identify patterns and main themes that emerged from the interviews. The results showed that environmental factors, such as peer influence and social media, as well as social pressure to look “mature” are the main triggers of smoking behavior in adolescent girls. In addition, a low understanding of the long-term health risks also contributes to their decision to smoke. However, some adolescents showed awareness of the dangers of smoking, although not strong enough to kick the habit. The conclusion of this study is that more comprehensive interventions are needed, focusing on health education aimed specifically at adolescent girls, as well as controlling social influences that encourage smoking behavior.